2012
DOI: 10.1001/jama.2011.2035
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole for Children With Poorly Controlled Asthma: A Randomized Controlled Trial

Abstract: Context Asymptomatic gastroesophageal reflux (GER) is prevalent in children with asthma. It is not known whether treatment of GER with a proton-pump inhibitor (PPI) improves asthma control. Objective To determine whether lansoprazole is effective in reducing asthma symptoms in children without overt GER. Design, Setting, and Patients A multicenter, randomized, masked, placebo controlled, parallel clinical trial comparing lansoprazole to placebo in children with poor asthma control on inhaled corticosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(113 citation statements)
references
References 37 publications
6
102
1
4
Order By: Relevance
“…Gastro-oesophageal reflux (GOR) is present in 60-80% [15,23,120,141,144], but clinical trials with antireflux therapy generally show little to no effect on asthma control [145][146][147]. The role of ''silent'' GOR disease (GORD) as a cause of poor asthma control in general may be over-emphasised, but the child with gastrointestinal symptoms and problematic asthma should be evaluated and treated for GORD [147].…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastro-oesophageal reflux (GOR) is present in 60-80% [15,23,120,141,144], but clinical trials with antireflux therapy generally show little to no effect on asthma control [145][146][147]. The role of ''silent'' GOR disease (GORD) as a cause of poor asthma control in general may be over-emphasised, but the child with gastrointestinal symptoms and problematic asthma should be evaluated and treated for GORD [147].…”
Section: Remarksmentioning
confidence: 99%
“…The role of ''silent'' GOR disease (GORD) as a cause of poor asthma control in general may be over-emphasised, but the child with gastrointestinal symptoms and problematic asthma should be evaluated and treated for GORD [147]. Although the impact of treatment of sinusitis and GORD on severe asthma is not yet clear, when these comorbidities are present, they should be treated as appropriate to improve these conditions.…”
Section: Remarksmentioning
confidence: 99%
“…A recent met-analysis of 26 studies reported 49% increase in the risk of community acquired pneumonia, which was at its highest during the first 30 days of PPI initiation [82]. Data also have shown associations between PPIs and increased upper respiratory tract infections and asthma exacerbation in pediatric population [83,95]. …”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…7,8 Indeed, in a recent study in children with poorly controlled asthma, no gastrointestinal symptom differentiated those with and without GER identified by oesophageal pH monitoring. 9 Taken together, these findings emphasise that the prevalence of GERD in asthmatic children identified in studies that used symptom scores as inclusion criteria and/or endpoints is likely biased by the inability to differentiate symptoms of asthma from those of GER.…”
Section: Exploring the Association Between Asthma And Gastroesophageamentioning
confidence: 86%